Brazilian consensus on photoprotection - Schalka, Sérgio; Steiner, Denise; Ravelli, Flávia Naranjo; Steiner, Tatiana; Terena, Aripuanã Cobério; Marçon, Carolina Reato; Ayres, Eloisa Leis; Addor, Flávia Alvim Sant'anna; Miot, Hélio Amante [UNESP]; Ponzio, Humberto; Duarte, Ida; Neffá, Jane; et al. (FapUNIFESP (SciELO), 2014)
Brazil is a country of continental dimensions with a large heterogeneity of climates and massive mixing of the population. Almost the entire national territory is located between the Equator and the Tropic of Capricorn, and the Earth axial tilt to the south certainly makes Brazil one of the countries of the world with greater extent of land in proximity to the sun. The Brazilian coastline, where most of its population lives, is more than 8,500 km long. Due to geographic characteristics and cultural trends, Brazilians are among the peoples with the highest annual exposure to the sun. Epidemiological data show a continuing increase in the incidence of non-melanoma and melanoma skin cancers. Photoprotection can be understood as a set of measures aimed at reducing sun exposure and at preventing the development of acute and chronic actinic damage. Due to the peculiarities of Brazilian territory and culture, it would not be advisable to replicate the concepts of photoprotection from other developed countries, places with completely different climates and populations. Thus the Brazilian Society of Dermatology has developed the Brazilian Consensus on Photoprotection, the first official document on photoprotection developed in Brazil for Brazilians, with recommendations on matters involving photoprotection.

Brazil is a country of continental dimensions with a large heterogeneity of climates and massive mixing of the population. Almost the entire national territory is located between the Equator and the Tropic of Capricorn, and the Earth axial tilt to the south certainly makes Brazil one of the countries of the world with greater extent of land in proximity to the sun. The Brazilian coastline, where most of its population lives, is more than 8,500 km long. Due to geographic characteristics and cultural trends, Brazilians are among the peoples with the highest annual exposure to the sun. Epidemiological data show a continuing increase in the incidence of non-melanoma and melanoma skin cancers. Photoprotection can be understood as a set of measures aimed at reducing sun exposure and at preventing the development of acute and chronic actinic damage. Due to the peculiarities of Brazilian territory and culture, it would not be advisable to replicate the concepts of photoprotection from other developed countries, places with completely different climates and populations. Thus the Brazilian Society of Dermatology has developed the Brazilian Consensus on Photoprotection, the first official document on photoprotection developed in Brazil for Brazilians, with recommendations on matters involving photoprotection.
Keywords: Dermatology; Protection; Solar radiation; Sun protection factor